The ministry crisis from an analysis of prophet Elijah’s crisis in 1 Kings 19.1-18 - Klabunde, Rafael; Krüger, Rolf Roberto (Vox Scripturae - Revista Teológica Internacional, 2016)
This rehearsal’s purpose is to examine the subject ministry crisis from an analysis of 1 Kings 19.1-18. In this passage, Elijah, an important prophet, experiences God’s abscondence in his ministry. Even though Elijah is many times seen as a hero, overburden, loneliness and death wish can be observed in this story nevertheless. It is premised that, from Elijah’s experience, narrated on the mentioned passage, it is possible to apply important lessons to the reality which many caregivers experience nowadays. The said caregivers, very often seen as steadfast, are subject to suffering and need attention. Throughout the article, the various reasons that can lead a caregiver to crisis will be discussed, based on Elijah’s experiences, such as fatigue, disappointment with the people of God and other factors. Finally, the necessity of attention to the caregivers will be approached, as well as the way this attention occurred in the prophet’s experiences, through the act of God.